The Use of Mirnas as Activators of Dental Implant Surfaces, A Review - Di Gianfilippo Riccardo (International Journal of Bone and Mineral Metabolism, 2018)
MicroRNAs are short sequences of non-coding RNAs crucial in regulation of cell development, proliferation and differentiation. Some of them showed to be related with the expression of osteogenic genes. Aim of the present review was to evaluate the biological effects of titanium implant surfaces activated with miRNAs or antimiRNAs. A bibliographical electronic research was carried out on PubMed/Medline. Articles investigating the influences of miRNA functionalized surfaces on human or animal cells were included. Reports were excluded if investigating surfaces modified with molecules different from miRNAs, if miRNAs were not loaded to titanium surfaces. Five articles met the inclusion criteria. Surfaces functionalized with miRNAs showed to up-regulate the expression of osteogenic genes like RUNX2, OPN, OCN, BMP, OSX, ALP, COL1 and COL3. Investigated surfaces additionally showed more bone-like mineralized tissues, bone lacunae, osteocytes and new blood vessels. MiRNAs loaded to titanium implant surfaces stimulate the expression of genes related to osteoblasts differentiation, osteogenesis, osseointegration and reparation of mineralized tissues. Vectors used to link titanium surfaces and miRNAs did not show cytotoxicity or interference with cells’ viability.
Keywords: miRNA